Pelaksanaan Zakat Hasil Penjualan Karet Di Desa Paku Kecamatan Payung Kabupaten Bangka Selatan Menurut Hukum Islam - Husnul Badri; Ahmad Afif (Indonesian Journal of Islamic Law, 2021)
In Indonesia, the majority of muslims, zakat becomes an integral aspect of life. In order to fulfill one of the obligations contained in the pillars of Islam, that is to pay zakat as an expressions pf the form of gratitude Atad favor that has been given by Allah SWT. From several types of zakat, one of them is the charity sales result of rubber. Rubber farmers in the village paku many who do not know of thr result of the rubber sales zakat and to issue zakat in accordance with thr provisions of Islamic Shariah. Departing from this background, the author is then interested to do research with the title of the study of Zakat Analysis of Rubber Sales Result (Case Study in The Village of Paku Subdistrict Payung District of South Bangka). The purpose of this researc is yo know how the provisions for issuing the rubber sales result in the perspective of Islamic law. In this study, the research type is field research with the method of data collection through interviewing (interview). While analyzing the data, the steps involved include data reductions, data presentation, and withdrawal of conclusions. The results of the research conducted by the authors can be submitted in the Village of Paku subdistrict Payung District of South Bangkais still not done zakat results rubber sales as it should. In fact, when viewed in terms of the result obtained, every time the harvest has fufilled the provision to be issud zakat. This is because the people or rubber farmers in Paku Village are still confused in the calculation to issue a zaat on rubbersales. According to the perspective of Islamic law, the proceed of the rubber sales are obliged to be issued when it reaches Nisab or already entered in the expenditure of trede zakat according to Islamic law. Keyword : Analysis Study, Rubber Zakat